2020
DOI: 10.21203/rs.3.rs-107991/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Affecting Family Planning Literacy: Perspectives of Women of Childbearing Age in Rural Lake Zone, Tanzania

Abstract: Background Low uptake of various recommended modern family planning methods is associated with inadequate family planning literacy among potential beneficiaries of the methods. As such, understanding the factors affecting family planning literacy is key to addressing this problem. This study, therefore, explored factors affecting family planning literacy of women of childbearing age in the rural Lake Zone of Tanzania.Methods The study utilized an exploratory descriptive qualitative research approach using focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, studies have reported a significant association between marital status and health information literacy (Kassim and Ndumbaro, 2020; Mbekenga et al, 2021; Muhanga and Malungo, 2018). In these studies, women who are married are reported to have higher levels of health information literacy compared with those who are not married.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have reported a significant association between marital status and health information literacy (Kassim and Ndumbaro, 2020; Mbekenga et al, 2021; Muhanga and Malungo, 2018). In these studies, women who are married are reported to have higher levels of health information literacy compared with those who are not married.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Benard and Chipungahelo, 2017; Heijmans et al, 2015; Hirvonen, 2015; Mahdizadeh and Solhi, 2018; Mojoniyola, 2011; Zimmerman, 2017), research in this area, particularly in developing countries like Tanzania, is scarce. Only a few studies have specifically assessed the health information literacy skills of women of childbearing age in rural Tanzania (see Kassim and Ndumbaro, 2020; Mbekenga et al, 2021). Other available studies on health information literacy in Tanzania have focused on medical librarians (Haruna et al, 2017) and health-care providers and agricultural officers (Wema, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%